Pengaruh Good Corporate Governance terhadap Kinerja Lembaga Wakaf di Indonesia - Setiawan, Nanang (Journal of Islamic Finance and Syariah Banking, 2024)
Amid the growing focus on transparency and accountability in the management of waqf institutions in Indonesia, implementing Good Corporate Governance (GCG) has become crucial for ensuring optimal and sustainable performance. This study aims to examine the influence of GCG on the performance of waqf institutions in Indonesia. The data for this research were collected through questionnaires distributed to Waqf Nazhir under the supervision of the Indonesian Waqf Board (BWI). A total of 125 waqf Nazhir participated in the survey. The results show that GCG significantly impacts the performance of waqf institutions in Indonesia. This study provides empirical evidence that implementing GCG principles can significantly enhance the performance of waqf institutions, thereby contributing to more effective and transparent waqf asset management. The findings offer valuable insights for waqf managers on the importance of GCG and can serve as a reference for the BWI and policymakers in formulating guidelines and policies that support better governance of waqf institutions in the future.